PENGALEH PUKOL Komposisi Karawitan Kesenian Kompang Di Desa Concong Luar Kabupaten Indragiri Hilir - Rizki Agus Irlianto; M. Halim M. Halim; Firman Firman (Laga-Laga : Jurnal Seni Pertunjukan, 2022)
ABSTRACTKompang art in Concong Luar Village, Concong Subdistrict, Indragiri Hilir Regency, in the kompang pattern game on the long pukol song, the kompang pattern is played with manners and the musical structure of the work is still underdeveloped. From this musical case, the artist got the idea to develop a kompang transition pattern that is still underdeveloped to be varied both in terms of sound color and rhythm pattern. the creator was inspired by the transition pattern in the long pukol song. Pengaleh Pukol is a term that the author adopted from the mention of the transitional pattern in the long pukol song. From the kompang transition pattern, the artist develops transitional patterns in the kompang found in the long pukol song with a new composition that is different from the tradition. Based on the artist's observations of the transitional pattern, this has still not been worked out in a variety of ways, so the idea arose from the artist to work on the Riau Kompang art into compositional work with a traditional approach, with several instruments such as, rabano, kompang, and flying as a form of developing work as well as a touch of taste. varied and unobtrusive.